The “devil” you don't know: A test of the detriments and benefits of co-founding with strangers - Greenberg, Jason; Mollick, Ethan (Journal of Business Venturing, 2026)
One key to new venture creation and success is getting the “people part” right. Professional investors have a strong preference for funding founding teams of people rather than individuals. This preference is based on the belief that starting a new venture requires a portfolio of experiences, skills, and networks that few individuals possess. Implicit in this thesis is the belief that the benefits of a team outweigh its costs that can accrue with co-founders arising from information asymmetries. Such information asymmetries are greater when founding with strangers given an absence of prior relational experience. Yet, strangers are more likely capable of providing the theorized (unique) value-add of co-founders such as non-redundant networks. Unfortunately, due to data limitations, the literature has not assessed assumptions concerning the pros/cons of co-founding with strangers thereby limiting our ability to get the people part of new ventures “right.” We use unique survey data on more than three thousand new ventures that successfully launched a crowdfunding campaign to assess these assumptions. These survey data include enough teams with strangers and granular measures of team functioning, product/service delivery, and operational status for comprehensive assessments. Results reveal that new ventures including strangers on the team are less likely to deliver the product/service they pitched and are more likely to be non-operational. Direct, descriptive evidence suggests that team-related issues underlie these outcomes.